Z Proteins of New World Arenaviruses Bind RIG-I and Interfere with Type I Interferon Induction - Fan, Lina (American Society for Microbiology (ASM), 2010)
The retinoic acid-inducible gene I product (RIG-I) is a cellular sensor of RNA virus infection that regulates the cellular beta interferon (IFN-β) response. The nucleoproteins (NP) of arenaviruses are reported to antagonize the IFN response by inhibiting interferon regulatory factor 3 (IRF-3). Here, we demonstrate that the Z proteins of four New World (NW) arenaviruses, Guanarito virus (GTOV), Junin virus (JUNV), Machupo virus (MAVC), and Sabia virus (SABV), bind to RIG-I, resulting in downregulation of the IFN-β response. We show that expression of the four NW arenavirus Z proteins inhibits IFN-β mRNA induction in A549 cells in response to RNA bearing 5′ phosphates (5′pppRNA). NW arenavirus Z proteins interact with RIG-I in coimmunoprecipitation studies and colocalize with RIG-I. Furthermore, expression of Z proteins interferes with the interaction between RIG-I and MAVS. Z expression also impedes the nuclear factor kappa light chain enhancer of activated B cells (NF-κB) and IRF-3 activation. Our results indicate that NW arenavirus Z proteins, but not Z protein of the Old World (OW) arenavirus lymphocytic choriomeningitis virus (LCMV) or Lassa virus, bind to RIG-I and inhibit downstream activation of the RIG-I signaling pathway, preventing the transcriptional induction of IFN-β.